Social and geographical inequalities in school starting age in Australia: a population data linkage study: IJPDS (2017) Issue 1, Vol 1:101, Proceedings of the IPDLN Conference (August 2016) - Hanly, Mark; Falster, Kathleen; Craven, Rhonda; Jorm, Louisa (International Journal of Population Data Science, 2017)
ABSTRACT Objective In Australia’s most populous state, New South Wales (NSW), children must start school in the year they turn five, unless they are born between February-July, in which case they can delay starting until the year they turn six. Consequently, children start their first year of school aged 4.5-6 years. This may translate into a wide range of developmental ability in the classroom in the first year of school and may impact on the magnitude of inequalities in longer-term educational outcomes. To inform how this policy currently translates into the demographic composition of NSW classrooms, this study aims to identify child, family, and area-level characteristics associated with the practice of delaying school entry. Approach The ‘Seeding Success’ study cohort (N=154,936) includes an almost complete population of children who started school in NSW in 2009 or 2012, and were born in NSW, identified by linking the Australian Early Development Census (AEDC) data to perinatal and birth registry data. Restricting this analysis to the 88,716 (57%) children born in February-July, we defined ‘delayed school entry’ as children who were eligible to start school the previous year (i.e. 2008 or 2011), but started in the AEDC data collection years (i.e. 2009 or 2012). Multilevel regression models were used to investigate child, family and area-level characteristics associated with delayed school entry. Results The prevalence of delayed school entry was 46% in the 2009 AEDC cohort and 47% in the 2012 AEDC cohort. Boys and children born closer to July were more likely to be delayed, as were children of older mothers. Prevalence of delay was similar in Aboriginal and non-Aboriginal children, however, children of mothers born overseas were less likely to delay school entry compared to Australian-born mothers. Delaying was less common in major cities compared to remote and regional areas, and less common in socio-economically disadvantaged areas. Conclusion Children born in February-July who live in socio-economically disadvantaged urban areas are more likely to start school up to a year earlier than their peers, with poorly understood educational consequences. The current policy on school starting age results in an 18-month age range in classrooms, which may be challenging for teachers and confusing for parents who need to make a decision regarding their child’s ‘school readiness’. It is likely that access and affordability of childcare during the study period impacted on parent’s decisions about when to send their children to school.